Analysis of the Risk Management of Purchasing Puri Nirana Cigelam Sharia Housing in the Perspective of Islamic Economics - Adriansah, Adriansah; Sya’ban, Muhammad Fauzan Nur; Adisty, Elfara; Apriani, Eka (International Conference on Islamic Economic (ICIE), 2023)
As a housing developer, Puri Nirana Cigelam (PNC) Purwakarta, West Java, offers housing with a sharia concept or sharia housing. Sharia housing carries a Sharia system in its financing contracts without the involvement of Sharia or conventional banks. The purpose of this study is to first analyze the risk management of contract implementation in buying and selling housing at PNC. Second, analyzing the application of risk management in the sale and purchase of Sharia housing loans at PNC. Third, analyze the adherence to Islamic economics principles in applying risk management in PNC. This research is qualitative. At the same time, technical data mining using interviews and observation. Technical data processing by editing, organizing, and discovering results and data analysis obtained descriptively to draw conclusions. The study results in show that the risk management carried out at PNC in its sharia contracts is running well even though it is relatively new and outside property developers' customs and habits in risk management. Risk management in implementing buying and selling credit at PNC is going well for risk policies with a Sharia approach. The principles of Islamic economics also colour the existing risk management policies in PNC Sharia housing; there are elements and values ​​of Sharia economic principles that are quality, non-exploitative, free of usury, prosperous and spiritually valuable.